KONTRIBUSI KOMODITAS PERTANIAN TERHADAP INFLASI DI KOTA MANADO TAHUN 2019 - Angelita Monica Leiley; Jean Fanny Junita Timban; Olly Esry Haryani Laoh (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the effect of agricultural commodities on inflation in the city of Manado and what agricultural commodities have a significant effect on inflation in the city of Manado. This research was conducted in December 2019 until February 2020. Data collection was obtained through secondary data obtained from the Central Statistics Agency of North Sulawesi Province which was taken through the official website of BPS North Sulawesi Province. Sampling uses a time series data source. Data analysis uses multiple linear regression analysis methods. This analysis will produce a pattern and closeness of the relationship between the dependent variable and the independent variable, estimate the effect of the independent variable on inflation in the city of Manado, and be able to predict inflation in the city of Manado if the magnitude of the independent variable is known. The results showed that the Manado City Inflation was influenced by agricultural commodities, namely vegetables, legume inflation, fruit inflation and seasoning inflation. Grain groups have no effect on inflation in the City of Manado.*eprm*